2020
DOI: 10.4251/wjgo.v12.i7.741
|View full text |Cite
|
Sign up to set email alerts
|

Maspin subcellular expression in wild-type and mutant TP53 gastric cancers

Abstract: BACKGROUND Although the role of p53 in the evolution and prognosis of gastric cancer (GC) has been extensively examined, the exact mechanism of action is incompletely understood. In the last years, p53-target genes were supposed to be involved in the p53 pathway. One of them is the tumor-suppressor gene Maspin, which codifies the protein with the same name. Maspin activity depends on its subcellular localization. To our knowledge, the possible role of TP53 gene in Maspin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The results indicated that, although recommended as classic markers in CRC, not all of the five loci in the B5 panel were sensitive to MSI in GC. In addition, TP53-1 was considered to be the most LOH-prone locus, which was in line with a previous study, which suggested that TP53 was the most mutated gene (18).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results indicated that, although recommended as classic markers in CRC, not all of the five loci in the B5 panel were sensitive to MSI in GC. In addition, TP53-1 was considered to be the most LOH-prone locus, which was in line with a previous study, which suggested that TP53 was the most mutated gene (18).…”
Section: Discussionsupporting
confidence: 88%
“…It is well-known that the alteration of tumor-related genes, such as the inactivation of tumor suppressor (TS) genes and the amplification of oncogenes, is a main factor in GC development ( 18 , 19 ). On the other hand, MSs are frequently used as markers for the detection of loss of heterozygosity (LOH), which has been associated with GC progression ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of TP53 may upregulate vascular endothelial growth factor A (VEGF-A) expression and promote cancer cell angiogenesis, leading to a poor prognosis ( 36 ). Gurzu et al ( 37 ) analyzed a large number of human gastric cancer samples and found that mutation of exon 7 in TP53 may induce downregulation of the expression of the tumor suppressor gene Maspin, which leads to GC invasion and metastasis. In addition, TP53 mutations induce hypoxic signaling ( 38 ) and inhibit antitumor immunity ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maspin is a p53-target gene which also depends on the microsatellite status of the tumor cells [1,15,19,20]. In gastric carcinomas, we proved that loss of maspin might be induced by TP53 gene mutations in exon 7 whereas wild-type p53 was hypothesized to be responsible by restoration of the nuclear maspin expression and further decreasing of the metastatic potential [20].…”
Section: Maspin Expression In Malignant Tumorsmentioning
confidence: 81%